SIMULATION OF THE EFFECT OF RACKS ON COILED TUBING USING ANSYS: ،،، - Benaros, M. (Conference On Engineering Science and Technology, 2021)
One of the main causes of failure and breakdown Coiled Tubing (CT) is often cracks. In this study, the Stress Intensity Factor (SIF)  was found using ANSYS program and it was compared with the Stress Intensity Critical Factor  of (CT). This is to determine the extent to which pipes that carry small cracks can be used or not. Simulations were carried out on CT-130 Coiled Tubing containing cracks. A relationship is plotted between   and (a/t). The results obtained were identical with the results of the research ( Cassa, A. M. (2010), ) Alshoaibi, A. M. (2019). The results of the tensile and bending strength on samples bearing transverse cracks show that the use of loads more than 60 KN and crack depth greater than 35% of the wall thickness causes the pipe to enter the plastic area, where the possibility of collapse is high. In the case of longitudinal faults, they are considered more stable, as the results show that the bearing strength reaches 150 KN when the fault depth is less than 35%. On the other hand, it can be said that a collapse of the tube occurs when . At levels where it is the material will deform plastically to absorb the applied force. The pipe can be operated in conditions where  taking into account a safety ratio of not less than 20%
Keywords: Mechanical properties; Stress intensity factor; cracks; Striations; Coiled tubing; Ansys